Association of interleukin‐10‐1082 (‐1087) A > G polymorphisms and periodontitis risk: An updated meta‐analysis based on 26 case‐control studies. (21st June 2019) - Li, Yao; Hu, Bo; Feng, Ge; Chen, Qian; Zhu, Mengyuan; Ying, Siqi; Song, Jinglin
Abstract: Background: The association between interleukin‐10 (IL‐10)‐1082 (‐1087) A > G polymorphism and either chronic (CP) or aggressive periodontitis (AgP) susceptibility was conflicting. This meta‐analysis aimed to quantitatively estimate the association. Methods: Pubmed, Embase, Web of Science, and WANFAN databases were searched for relevant studies that were submitted prior to January 31, 2018, and meta‐analyses were performed using STATA 14.0. Results: Database mining yielded 26 studies of interest. For the IL‐10‐1082 (‐1087) A > G (rs1800896) polymorphism and its relation to CP susceptibility, the overall analysis showed no significant estimates, but subgroup analysis revealed significant associations in the AA versus GG + GA model in the Caucasian population (odds ratio [OR] = 1.274, 95% confidence interval [CI] = 1.069–1.518, P  = 0.007; I 2  = 0.0%, P  = 0.483) and in the GG versus AA + AG model in the Han population (OR = 6.66, 95% CI = 7.72–9.41, P  = 0.000; I 2  = 0.0%, P  = 0.82), which all showed no obvious publication bias by Egger's linear regression test. For the association between an IL‐10‐1082 (‐1087) A > G polymorphism and AgP susceptibility, the overall analysis and Caucasian subgroup analysis yielded nonsignificant estimates. Conclusions: Our meta‐analysis indicated that the IL‐10‐1082 (‐1087) AA genotype in the Caucasian population, and the GG genotype in the Han population might be putative risk factors for CP. Practical implications: The IL‐10‐1082 (‐1087) AA genotype and the GG genotype might be potential biomarkers for Caucasian CP and for Han CP, respectively. However, additional research will be required to validate the findings of this meta‐analysis.